Critical retinal disease detection from optical coherence tomography images by deep convolutional neural network and explainable machine learning - Datta, Pranab; Islam, Saniul; Das, Retuparna; Zabir, Mihiran Uddin (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.